Solution behaviour of rivanol in micellar environments - ÇAKIR, NEŞE; CANTÜRK TALMAN, REMZİYE YEŞİM; GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2006)
the interaction of the cationic drug rivanol (RIV) with three types of surfactants; [cationic (cetyltrimethylammonium bromide; CTAB), anionic (sodium dodecylsulfate; SDS), and nonionic (t-octylphenoxypolyethoxyethanol, TX-100)] has been studied spectrophotometrically as a function of surfactant concentration from the premicellar to the postmicellar region. A comparison of the binding constants calculated from the Benesi-Hildebrand equation indicated that the binding tendency of RIV with TX-100 micelles is higher than that with SDS micelles. The binding constants of RIV to both SDS and TX-100 micelles were found to decrease in the presence of NaCl (0.225% w/v), ethanol (5% v/v), propylene glycol (5% v/v), and glycerin (5% v/v), The addition of the additives to the medium had a pronounced effect on the association of RIV with micelles. They all tended to decrease the binding of RIV to micelles. The inhibitory effect of alcohols followed the order water > glycerin > propylene glycol > ethanol.
Keywords: binding constant; cosolvent; interaction; micelles; rivanol; surfactants; AMPHIPHILIC HEMICYANINE DYES; SODIUM DODECYL-SULFATE; SURFACTANT SOLUTIONS; CATIONIC SURFACTANT; ANIONIC SURFACTANT; IONIC SURFACTANTS; ABSORPTION-SPECTROSCOPY; AQUEOUS-SOLUTIONS; METHYL-ORANGE; CACO-2 CELLS